2023
DOI: 10.1021/acsami.2c19729
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strain Engineering Combined with a Microscopic Pore Synergistic Modulated Strategy for Designing Lattice Tensile-Strained Porous V2C-MXene for High-Performance Overall Water Splitting

Abstract: Transition metal carbon/nitride (MXene) holds immense potential as an innovative electrocatalyst for enhancing the overall water splitting properties. Nevertheless, the re-stacking nature induced by van der Waals force remains a significant challenge. In this work, the lattice tensile-strained porous V 2 C-MXene (named as TS (24) -P (50) -V 2 C) is successfully constructed via the rapid spray freezing method and the following hydrothermal treatment. Besides, the influence of lattice strain degree and microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…Different from NFF, corrosion-engineered NFF (5:5) -LDH (6) /Fe 2 O 3 and combustion-grown C-NFF (5:5) -LDH (6) /Fe 2 O 3 displayed obvious hysteresis at relatively high pressures ( P / P 0 > 0.4), indicating a mesoporous structure given by the vertical nanosheet array on top of the macroporous NFF substrate. The unique heterojunction/mesoporous structure endows C-NFF (5:5) -LDH (6) /Fe 2 O 3 with a continuous ion diffusion path for short transport, beneficial for cycle stability . The FTIR spectra (Figure c) demonstrate that the strong characteristic peak of CO 3 2– at around 1370 cm –1 in NFF (5:5) -LDH (6) /Fe 2 O 3 still remained after combustion, suggesting that the carbonate moiety might stem from the atmospheric environment.…”
Section: Resultsmentioning
confidence: 99%
“…Different from NFF, corrosion-engineered NFF (5:5) -LDH (6) /Fe 2 O 3 and combustion-grown C-NFF (5:5) -LDH (6) /Fe 2 O 3 displayed obvious hysteresis at relatively high pressures ( P / P 0 > 0.4), indicating a mesoporous structure given by the vertical nanosheet array on top of the macroporous NFF substrate. The unique heterojunction/mesoporous structure endows C-NFF (5:5) -LDH (6) /Fe 2 O 3 with a continuous ion diffusion path for short transport, beneficial for cycle stability . The FTIR spectra (Figure c) demonstrate that the strong characteristic peak of CO 3 2– at around 1370 cm –1 in NFF (5:5) -LDH (6) /Fe 2 O 3 still remained after combustion, suggesting that the carbonate moiety might stem from the atmospheric environment.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of low crystalline species likely causes the lattice of FeOOH to produce tensile strain. 37…”
Section: Resultsmentioning
confidence: 99%
“…S19, ESI†), it is found that the lattice has an obvious tensile distortion. 55 This distortion may be due to the synergistic effect between the two metals, which changes the corresponding coordination environment, and results in lattice distortion. The results presented here fully prove the formation of low crystalline FeCoOOH.…”
Section: Resultsmentioning
confidence: 99%